Adsorption of water, sulfates and chloride on arsenopyrite surface - Silva, Juliana C. M.; Dos Santos, Egon C.; De Oliveira, Aline; Heine, Thomas; De Abreu, Heitor A.; Duarte, Helio A. (Applied Surface Science, 2018)
Arsenopyrite is one of the sulfide minerals responsible for acid rock drainage (ARD) and is one of the most hazardous in regions affected by mining activities. This phenomenon involves complex reaction mechanism. Although it is intensely investigated, there is a lack of consensus concerning the reaction mechanisms and more information is still necessary. In this work, the adsorption of water, hydrochloric acid, and sulfuric acid on arsenopyrite (001) surface was investigated by means of Density Functional calculations and the results compared to other sulfides aiming to understand the mineral/water interface. The interaction of the chemical species with the (001) FeAsS surface is the first step to understand the intricate oxidation mechanism of arsenopyrite. Molecular water adsorption on (001) FeAsS is more favored than the adsorption of sulfate favoring the dissolution of sulfates and enhancing its oxidation. The estimated adsorption energies of water, sulfates and chloride on other sulfide minerals are compared with the estimated values for arsenopyrite and the chemical reactivity differences discussed in detail.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Adsorption; Arsenopyrite; Density functional theory; Plane waves; Sulfates; Sulfide minerals